Seed coat phytochemistry of both resistant and susceptible seeds affords some protection against the granivorous beetle Callosobruchus maculatus. (December 2017) - Hudaib, Taghread; Hayes, William; Brown, Sarah; Eady, Paul E.
Abstract: The seed coat lies at the interface between the internal structures of the seed and the external environment and thus represents a key arena in the study of seed-herbivore interactions. Callosobruchus maculatus is a cosmopolitan pest of legume seeds, and under post-harvest conditions, females interact directly with the seed testa prior to laying their eggs. Here we investigate the effect of chemical extracts of the seed coat of the resistant Phaseolus vulgaris and the susceptible Vigna unguiculata beans on egg laying preferences and larval development of C. maculatus . Seed coat extracts contained phenolic, glycoside and alkaloid compounds. Upon re-incorporation of extracts into artificial host beans it was found that that several seed coat extracts from both the resistant and susceptible varieties reduced female oviposition and disrupted larval growth and development. However, none of the extracts assayed resulted in complete ovipositional or developmental failure suggesting that complete resistance in P. vulgaris is derived from other physical or chemical properties of the seed and/or seed coat that function either alone or synergistically. Further work is required to elucidate the importance of synergistic interactions between different physiological defence mechanisms on overall plant (seed) resistance.